Water needs for various investments in the Nile side in a governorate in Babylon - Niema, Jehan Ali Abed; Al-Ibrahimi, Suhaila Najem (Al-Adab Journal, 2022)
After the research dealt with the location of the study area and the main problem was identified, the research talked about the demographic aspect and its impact on ground and surface water from the aspect of consumption and investment, and then the agricultural aspect by showing the agricultural density in the region, the cultivated areas, its water needs, classification of water and its suitability for drinking and irrigation, then the research dealt with The aspect of animal consumption for drinking water, the need of aquatic animals for each year, the investment of water for fisheries, and finally the industrial aspect, which clarified the needs of each type of industries for water and touched upon the industries in the study area.